Irish Immigration in Springdale, Alexandria Township, Leavenworth County, Kansas, 1860 – 1907 - Baker, Zach (Kansas State University. Dept. of History, 2011)
The author describes the life of an early Irish Catholic settlement in eastern Kansas. Originally a Quaker community, Irish immigration "exploded" there just after the Civil War, eventually stamping the town with a particular religious culture. After railroads made the Fort Riley mail road obsolete, Springdale declined. St. Thomas Catholic Church was a vital center for decades.
Keywords: Leavenworth County; Springdale; Quakers; Irish Catholics; St. Thomas Catholic Church